Stability analysis of a proposed scheme of order five for first order ordinary differential equations / Sunday Emmanuel Fadugba, Roseline Bosede Ogunrinde and Rowland Rotimi Ogunrinde - Fadugba, Sunday Emmanuel; Ogunrinde, Roseline Bosede; Ogunrinde, Rowland Rotimi (Penerbitan UiTM, 2021)
This paper presents the stability analysis of a proposed scheme of order five (FCM) for first order Ordinary Differential Equations (ODEs). The proposed FCM is derived by means of an interpolating function of polynomial and exponential forms. The properties of FCM were discussed extensively. The linear stability of FCM in the context of the Third Order One-Step Method (TCM) and Second Order One-Step Method (SCM) for the solution of initial value problems of first order differential equations is presented. The stability region of FCM, TCM and SCM is investigated using the Dahlquist’s test equation. The numerical results obtained via FCM are compared with TCM and SCM. Moreover, by varying the step length, the accuracy and convergence of the methods in terms of the final absolute relative error are measured. The results show that FCM converges faster and more stable than its counterparts.